Osteoimmunology Interactions of the Immune and Skeletal Systems - Choi, Yongwon (Springer New York : Imprint: Springer, 2013)
This second edition of this book expands further on the first edition, which explored  the relationship between the human immune system and the skeletal structure. In the past, scientists involved in immune and bone-cell investigations have rarely interacted in a significant way, as these disciplines have developed independently and, for the most part, remain separate. This book brings together ideas of international scientists from both fields in pursuit of new collaborations. This may facilitate greater understanding  of the relationships between these fields.